Medical tourism in Malaysia: how can we better identify and manage its advantages and disadvantages? - Meghann Ormond; Wong Kee Mun; Chan Chee Khoon (Taylor & Francis Group, 2014)
Following the identification of medical tourism as a growth sector by the Malaysian government in 1998, significant government sector and private-sector investments have been channeled into its development over the past 15 years. This is unfolding within the broader context of social services being devolved to for-profit enterprises and 'market-capable' segments of society becoming sites of intensive entrepreneurial investment by both the private sector and the state. Yet, the opacity and paucity of available medical tourism statistics severely limits the extent to which medical tourism's impacts can be reliably assessed, forcing us to consider the real effects that the resulting speculation itself has produced and to reevaluate how the real and potential impacts of medical tourism are - and should be - conceptualized, calculated, distributed, and compensated for. Contemporary debate over the current and potential benefits and adverse effects of medical tourism for destination societies is hamstrung by the scant empirical data currently publicly available. Steps are proposed for overcoming these challenges in order to allow for improved identification, planning, and development of resources appropriate to the needs, demands, and interests of not only medical tourists and big business but also local populations.